(untitled) (Journal of the College of Basic Education, 2022)
This study aims to identify the effect of enrichment activities on the achievement of students of the Department of Family Education and Technical Professions subject in teaching methods, as the first chapter deals with the problem of research, the need for it, its importance and the aim of the study. As for the second chapter, it includes two topics, the first dealing with enrichment activities and the second on teaching methods. The third chapter deals with the search procedures. As the researcher followed the experimental method in studying the reality of two groups, the first is experimental and the other is control. The research community came from the students of the Department of Family Education and Technical Professions in the College of Basic Education, the third stage, and to achieve the goal of the research, the researcher renewed the enrichment activities (printed materials, television programs, slide programs ... etc.) and the researcher used a unit measurement tool (achievement test) to measure students’ achievement Two research groups (experimental and control). This test was characterized by validity and reliability, and appropriate statistical methods were used for the study (SPSS statistical bag), through which it showed the superiority of the students of M. T who studied enrichment activities on the students of M. Z who studied in the traditional way.